ANALYZING TOTALITARIANISM IN GEORGE ORWELL’S ‘1984’: PROPAGANDA, SURVEILLANCE, CONTROL, HISTORY, FEAR, AND SUPPRESSION - Putri, Apsari Eka; Nabila, Najwa Zayra; Faturrahman, Yanwar; Nurholis, Nurholis (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
George Orwell's 1984 is a dystopian novel that depicts a bleak future, incorporating elements of political totalitarianism. Where the society is fully controlled by the ruling regime. This is a fairly extreme political school, where a state fully controls all the personal lives of its citizens. This analysis focuses on the society in 1984. Propaganda carried out by the ruling party tries to shape the government according to its will and tries to erase the freedom of thought of its people. Surveillance of the people, starting from the content of thoughts, is under the control of the ruling regime. The manipulation of information and language is aimed at silencing the people from resisting the party. The violent terror portrayed in the novel is to enforce submission. George Orwell succeeded in illustrating how the politics of totaliarism, namely the bad consequences that will occur if this kind of political system is followed.